Madrasa Principal's Strategy in Improving the Quality of the Pandemic Era Learning Process at Madrasah Aliyah - Nurkhasanah, Umi; Barnoto, Barnoto; Hasan, Moch. Sya'roni; Ashari, Ashari; Sholeh, Rais Muhamad (Dirasah International Journal of Islamic Studies, 2023)
The research focused on the following questions with the hope of elucidating the methods used by the Head of Madrasah Aliyah Raudlatut Thalibin Bantungan Panarukan Situbondo to enhance the quality of the educational process: If you were to ask about the education system at MA Raudlatut Thalibin Bantungan Panarukan Situbondo, what would you say? (2) How does the principal of MA Raudlatut Thalibin Bantungan Panarukan Situbondo plan to enhance the educational experience for students in the Pandemic era? Qualitative methods were employed to describe the data. The researcher gathered information via interviews, field notes, and other first-hand accounts, as well as secondary sources that shed light on the topic at hand. Reducing data, presenting data, and drawing conclusions were the steps in this study's data analysis procedure. The following are the findings from studies conducted at MA Raudlatut Thalibin, Bantungan Panarukan, Situbondo: (2) Strategies for the Head of the Madrasa to apply in increasing the quality of the learning process at MA Raudlatut Thalibin, Bantungan Panarukan Situbondo; (1) the quality of the learning process has increased at MA Raudlatut Thalibin, Bantungan Panarukan Situbondo, during the pandemic period.